Analysis of the Principal's Leadership Strategy in Overcoming the Decline in Discipline of State Elementary School - Kholizah, Siti (Journal of Indonesian Progressive Education, 2026)
The principal's leadership strategy plays an important role in shaping a culture of discipline in the elementary school environment. In the face of the phenomenon of declining student discipline, school principals are required to apply a leadership style that is appropriate, collaborative, and responsive to the dynamics of students. This study aims to analyze the principal's leadership strategy in overcoming the decline in student discipline. This study uses a descriptive approach. Data collection methods with observation, interviews and documentation. The data analysis techniques are data reduction, data display, and data verification. The results of the study show that the leadership style strategy of the principal of SDN 0723 Parmainan uses democratic leadership, namely by providing examples or examples, giving advice, awards or sanctions. Participate in activities to provide guidance, supervision and direction. The level of discipline of students arriving on time was 47.30% while the level of discipline in dressing was 65.75%. In this case, the level of discipline based on the democratic leadership style is the right standard in overcoming the decline in discipline of public elementary school students 0723 Parmainan.